Photoelasticity in Dentistry: a literature review - Corrêa, Cássia Bellotto [UNESP]; Ribeiro, Ana Lúcia Roselino [UNESP]; Reis, José Maurício dos Santos Nunes [UNESP]; Vaz, Luis Geraldo [UNESP] (My University, 2014)
Introduction and Objective: Photoelasticity consists of an experimental technique of stress analysis. This technique is very used in most different areas including Dentistry. This literature review presents the several applications of photoelastic technique in Dentistry the several applications of photoelastic technique in Dentistry as well as its advantages and disadvantages. Literature review: Based on this method of analysis, it is possible the verification of the stress distribution and deformation in structures with complex geometry as maxilla and mandible. It can be used to evaluate the distribution of stress on several types of prosthesis as removable partial denture systems with different retention systems, conventional implant prosthesis, overdentures and Brånemark protocols. Moreover, photoelasticity can be used to assess the stress generated by various by various orthodontic movements, different orthodontic systems and different materials (orthodontic wires). In addition, it is used to analyze different defects of maxillectomy, splint types on traumatized tooth and post-core restoration methods. This technique can also be used to assess dental instruments such as evaluation of different designs of periodontal probe. Conclusion: The photoelastic analysis has been a technique of great importance in health area studies, more specifically in Dentistry. Based on this method of analysis, it is possible to measure the stress distribution and deformation in structures with complex geometry as maxilla and mandible.
Keywords: Biomechanics; Dental stress analysis; Dentistry